2019
DOI: 10.1111/1742-6723.13408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Victorian Emergency Minimum Dataset to medical records for emergency presentations for acute cardiovascular conditions and unspecified chest pain

Abstract: Objective The Victorian Emergency Minimum Dataset (VEMD) collects administrative and clinical data for all presentations to Victorian public ED. The present study aimed to examine the level of agreement between the VEMD data and the medical record for a sample of patients coded as having acute cardiovascular conditions (acute coronary syndrome, stroke and transient ischaemic attack [TIA]) and unspecified chest pain in the VEMD. Methods Six months of data provided to the VEMD from a large metropolitan hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…http://openheart.bmj.com/ Open Heart: first published as 10.1136/openhrt-2021-001792 on 18 October 2021. Downloaded fromCoronary artery disease accuracy in the data used in this study, particularly demographics, ACS diagnosis and EMS use 13. CONCLUSION Our findings suggest the NHFA's Warning Signs Campaign was associated with an increase in ACS ED presentations and EMS use, and a decrease in ED presentations via GPs.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…http://openheart.bmj.com/ Open Heart: first published as 10.1136/openhrt-2021-001792 on 18 October 2021. Downloaded fromCoronary artery disease accuracy in the data used in this study, particularly demographics, ACS diagnosis and EMS use 13. CONCLUSION Our findings suggest the NHFA's Warning Signs Campaign was associated with an increase in ACS ED presentations and EMS use, and a decrease in ED presentations via GPs.…”
mentioning
confidence: 63%
“…However, a validation study that we conducted in one centre showed high accuracy in the data used in this study, particularly demographics, ACS diagnosis and EMS use. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent audit data of the VEMD data set identified a concordance rate with emergency department (ED) medical records of 100% for index myocardial infarction diagnosis and 94% for index ACS diagnosis. 17 Consecutive patients attended by EMS for chest pain were included in the study if paramedics recorded either of the following criteria on the patient care record: (1) pain in the chest or central chest or (2) a final or secondary EMS diagnosis of ischemic chest pain, ACS, acute myocardial infarction, pleuritic pain, or angina. Exclusion criteria included traumatic chest pain, ST‐segment–elevation myocardial infarction (either prehospital or hospital discharge diagnosis), interhospital transfers, patient refusal to be transported to a hospital, death before EMS transport to a hospital, and age <18 years.…”
Section: Methodsmentioning
confidence: 99%